Comparison of hemodynamic responses to laryngoscopy and intubation using Macintosh or McCoy or C-MAC laryngoscope during uniform depth of anesthesia monitored by entropy - Rajasekhar, M. (J Anaesthesiol Clin Pharmacol, 2020)
BACKGROUND AND AIMS: Laryngoscopy forms an important part of general anesthesia and endotracheal intubation. The aim of the present study was to compare the hemodynamic responses to Laryngoscopy and Intubation using Macintosh or McCoy or C-MAC Laryngoscope with M-Entropy module monitoring to ensure uniform and adequate depth of anesthesia, during and after intubation. MATERIAL AND METHODS: A prospective, randomised, comparative study was done and patients included were of 18 to 60 years, ASA (American Society of Anesthesiologist) physical status I and II of both sexes undergoing elective surgery under general anesthesia. They were assigned to three groups using simple randomisation, after securing IV (intravenous) access, standard monitoring and Entropy leads were attached. General anesthesia was administered with glycopyrrolate 0.1 mg, fentanyl 2 ug/kg and intravenous thiopentone, 4 mg/kg. Adequate muscle relaxation was achieved with atracurium 0.6 mg/kg IV. By titrating isoflurane concentration, Entropy maintained between 40 and 60, orotracheal intubation done, with Macintosh or McCoy or C-MAC blades according to simple randomisation. Size of laryngoscope blade, time taken for laryngoscopy and intubation were noted. Heart rate, blood pressure, RE (Response Entropy) and SE (State Entropy) were noted before and during induction and laryngoscopy and post intubation up to 5 minutes. Statistical analysis done using NCSS 9 version 9.0.8 statistical software. RESULTS: Hemodynamic responses during laryngoscopy and intubation using Macintosh or McCoy or C-MAC laryngoscope were statistically insignificant (p > 0.05) between the three groups, provided the depth of anesthesia is maintained constant. CONCLUSIONS: It is the depth of anesthesia that decides the magnitude of hemodynamic responses and not the choice of laryngoscope.